2021
DOI: 10.1002/psp4.12582
|View full text |Cite
|
Sign up to set email alerts
|

PBPK Model of Coproporphyrin I: Evaluation of the Impact of SLCO1B1 Genotype, Ethnicity, and Sex on its Inter‐Individual Variability

Abstract: Coproporphyrin I (CPI) is an endogenous biomarker of OATP1B activity and associated drug-drug interactions. In this study, a minimal physiologically-based pharmacokinetic model was developed to investigate the impact of OATP1B1 genotype (c.521T>C), ethnicity, and sex on CPI pharmacokinetics and interindividual variability in its baseline. The model implemented mechanistic descriptions of CPI hepatic transport between liver blood and liver tissue and renal excretion. Key model parameters (e.g., endogenous CPI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 47 publications
6
36
0
Order By: Relevance
“…Males had greater concentrations of CPI and CPIII than females by 31 and 28%, respectively. The sex dependency on circulating CPI was previously reported in a cohort of Japanese subjects ( Mori et al, 2019 ) and is thought to be related to differences in synthesis rate ( Takita et al, 2020 ). In univariate analyses, East Asians had greater concentrations of CPI and CPIII compared to Caucasians ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 80%
“…Males had greater concentrations of CPI and CPIII than females by 31 and 28%, respectively. The sex dependency on circulating CPI was previously reported in a cohort of Japanese subjects ( Mori et al, 2019 ) and is thought to be related to differences in synthesis rate ( Takita et al, 2020 ). In univariate analyses, East Asians had greater concentrations of CPI and CPIII compared to Caucasians ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 80%
“…have reported that healthy Japanese individuals with OATP1B1*15/*15 alleles have higher CP‐I levels compared with those with OATP1B1*1b/*1b or OATP1B1*1b/*15 alleles. Takita et al 27 . have demonstrated that the hepatic activity of CP‐I is 79% lower in c.521CC compared with wild type, and 42% lower in Asian Indian patients compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanistic understanding of the disposition of biomarkers and factors contributing to inter-or intra-individual variability in their baseline is still lacking for many. This is of particular relevance for endogenous biomarkers for renal transporters, in contrast to more advanced knowledge and evaluation of endogenous biomarkers for hepatic transporters 3,15,20,24 . In this study a population PK model has been developed for PDA and HVA, two recently identified promising plasma-based biomarkers of renal transporters OAT1/3.…”
Section: Accepted Articlementioning
confidence: 99%
“…Modelling and simulation has increasingly been used as a tool to gain mechanistic insight into disposition of transporter biomarkers 3,14,[19][20][21][22][23][24] . These techniques are helpful in understanding the formation, disposition, and elimination process of endogenous biomarkers to facilitate their qualification and inform optimal design of subsequent interaction studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation